Cookie club : 80 creative cookies to make, swap, and share - Oniki, Mallory (Dorling Kindersley, 2026)
Mallory Oniki, creator of The Palatable Life, welcomes you to the Cookie Club, with this creative cookie cookbook packed with familiar favorites and unexpected flavor combinations Mallory Oniki's approach to baking is all about fun, flavor, and style. And when you join her Cookie Club, you'll never eat a lackluster cookie again. Each of the 80 cookie recipes in this book has been carefully chosen to inspire you to step outside your cookie comfort zone and make really good cookies at home, from classics like snickerdoodles and chocolate chip cookies (ten different kinds!) to new flavors like chili crisp cookies and date, cheddar, and dark chocolate cookies. Mallory teaches you the science behind baking the perfect cookie, making baking approachable and exciting for novice and experienced home bakers alike. Plus, she shares her tips for hosting cookie parties for any occasion, from Girls' Nights In to Holiday Parties and beyond. Cookie Club is a baking book for a new generation, with irresistible recipes that deliver on texture, flavor, and looks. Welcome to the Cookie Club!